10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Context Return-to-sport (RTS) decision-making is a pivotal phase in athletic rehabilitation, yet current practices are often fragmented and applied inconsistently. Inadequate interdisciplinary collaboration, misinterpretation of physician clearance, and systemic barriers contribute to suboptimal outcomes and elevated reinjury risk. The purpose of this review is to highlight critical knowledge gaps in RTS criteria and propose a multidisciplinary, biopsychosocial framework that integrates physical, psychological, and sport-specific readiness. The review emphasizes the importance of standardized yet individualized protocols, interdisciplinary communication, and foundational training knowledge. Evidence acquisition A narrative review was conducted using literature from sports medicine, rehabilitation, biomechanics, sport psychology, and performance science. Sources included peer-reviewed journals, consensus statements, and expert commentary. Key frameworks such as the Strategic Assessment of Risk and Risk Tolerance (StARRT) model and validated psychological screening tools were examined. References were accessed using Pubmed, Medline, and EBSCO with search criteria set between the year 2000 to the present, with the exception of 1 historical reference. Study design Clinical review. Level of evidence Level 3. Results Findings highlight that RTS decisions are often influenced by nonclinical pressures and lack standardized benchmarks. Psychological readiness is frequently underassessed, despite its significant impact on reinjury risk and performance. Integration of sport biomechanics, structured communication strategies, and interdisciplinary collaboration improves decision-making and athlete safety. Scalable models from elite sport settings demonstrate how tiered RTS frameworks and embedded psychological support can enhance outcomes across diverse environments, developmental stages, and care settings with limited resources or staffing. Conclusion RTS should be redefined as a collaborative, evidence-informed process that incorporates physical, psychological, and contextual factors. Standardization must support individualized care, with protocols tailored to sport, position, and developmental stage. By investing in education, interdisciplinary practice, and scalable technologies, clinicians can better support athletes through safer, more effective transitions back to sport.Strength-of-Recommendation Taxonomy (SORT):Grade B.